Proceedings of SPE California Regional Meeting 1987
DOI: 10.2523/16375-ms
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Effects of an Oil Phase on the Propagation of Foam in Porous Media

Abstract: Laboratory experiments were performed to determine the effects of a residual oil phase to hot nitrogen flood on the propagation of surfactant foam in Berea sandstone rocks.Static phase behavior-type tests were performed in support of the displacement tests.In the static experiments, surfactant partitioning into the oil phase and thermal degradation losses were measured. The chemical and physical properties of the oil phase were varied by the employment of four crude oil and two synthetic oil samples. The chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…The characteristics of foaming agents and oil samples used in the experiments may cause these differences. In general, it is commonly agreed that the presence of oil is detrimental to the foam stability [35,36,38,40], and our experimental results also support this view. Therefore, oil saturation is more likely to be regarded as an influencing factor of the resistance factor than a critical condition of foam collapse.…”
Section: Resistance Factor Vs Oil Saturationsupporting
confidence: 80%
See 1 more Smart Citation
“…The characteristics of foaming agents and oil samples used in the experiments may cause these differences. In general, it is commonly agreed that the presence of oil is detrimental to the foam stability [35,36,38,40], and our experimental results also support this view. Therefore, oil saturation is more likely to be regarded as an influencing factor of the resistance factor than a critical condition of foam collapse.…”
Section: Resistance Factor Vs Oil Saturationsupporting
confidence: 80%
“…Some studies have confirmed that the foam can be generated in the presence of oil by selecting appropriate foaming agents [31][32][33][34]. Some studies have stated that foam can be generated when the oil saturation is below a critical value [35][36][37], but some other studies have shown that foam is generated at relatively high oil saturation [34,38,39]. The characteristics of foaming agents and oil samples used in the experiments may cause these differences.…”
Section: Resistance Factor Vs Oil Saturationmentioning
confidence: 99%
“…The main purpose of these IFT measurements, however, was to evaluate the extent of IFT reduction with foaming solutions. Chaser SD1000 reduced the IFT between oil and water by a factor of about ten, as shown in [67] and Isaacs et al [64]. Even though I/I'S18 is a better IFT redacing agent, SD1000 was used in the oil displacement experiments because ot"its higher solubility and, therefore, better foa.mability at room temperature.…”
Section: 1mentioning
confidence: 91%
“…Jensen and Friedmann [67] reported oil-water interfacial tensio, ns by the pendent drop method of around 2-4 mN/m at 275°F for their system. This is about one tenth of the IFT between oil and water.…”
Section: 3513mentioning
confidence: 95%
See 1 more Smart Citation